First-line chemoimmunotherapy with bendamustine and rituximab versus fludarabine, cyclophosphamide, and rituximab in patients with advanced chronic lymphocytic leukaemia (CLL10): an international, open-label, randomised, phase 3, non-inferiority trial. Issue 7 (July 2016) - Eichhorst, Barbara; Fink, Anna-Maria; Bahlo, Jasmin; Busch, Raymonde; Kovacs, Gabor; Maurer, Christian; Lange, Elisabeth; Köppler, Hubert; Kiehl, Michael; Sökler, Martin; Schlag, Rudolf; Vehling-Kaiser, Ursula; et al.
Summary: Background: Chemoimmunotherapy with fludarabine, cyclophosphamide, and rituximab is the standard therapy for physically fit patients with advanced chronic lymphocytic leukaemia. This international phase 3 study compared the efficacy and tolerance of the standard therapy with a potentially less toxic combination consisting of bendamustine and rituximab. Methods: Treatment-naive fit patients with chronic lymphocytic leukaemia (aged 33–81 years) without del(17p) were enrolled after undergoing a central screening process. Patients were randomly assigned (1:1) with a computer-generated randomisation list using randomly permuted blocks with a block size of eight and were stratified according to participating country and Binet stage. Patients were allocated to receive six cycles of intravenous fludarabine (25 mg/m 2 per day) and cyclophosphamide (250 mg/m 2 per day) for the first 3 days or to intravenous bendamustine (90 mg/m 2 per day) for the first 2 days of each cycle. Rituximab 375 mg/m 2 was given intravenously in both groups on day 0 of cycle 1 and subsequently was given at 500 mg/m 2 during the next five cycles on day 1. The primary endpoint was progression-free survival with the objective to assess non-inferiority of bendamustine and rituximab to the standard therapy. We aimed to show that the 2-year progression-free survival with bendamustine and rituximab was not 67·5% or less with a corresponding non-inferiority margin of 1·388 for the hazard ratio (HR) based on the 90·4% CI. The final analysis was done by intention to treat. The study is registered withClinicalTrials.gov, numberNCT%2000769522 . Findings: 688 patients were recruited between Oct 2, 2008, and July 11, 2011, of which 564 patients who met inclusion criteria were randomly assigned. 561 patients were included in the intention-to-treat population: 282 patients in the fludarabine, cyclophosphamide, and rituximab group and 279 in the bendamustine and rituximab group. After a median observation time of 37·1 months (IQR 31·0–45·5) median progression-free survival was 41·7 months (95% CI 34·9–45·3) with bendamustine and rituximab and 55·2 months (95% CI not evaluable) with fludarabine, cyclophosphamide, and rituximab (HR 1·643, 90·4% CI 1·308–2·064). As the upper limit of the 90·4% CI was greater than 1·388 the null hypothesis for the corresponding non-inferiority hypothesis was not rejected. Severe neutropenia and infections were more frequently observed with fludarabine, cyclophosphamide, and rituximab (235 [84%] of 279 vs 164 [59%] of 278, and 109 [39%] vs 69 [25%], respectively) during the study. The increased frequency of infectious complications with fludarabine, cyclophosphamide, and rituximab was more pronounced in patients older than 65 years. Interpretation: The combination of fludarabine, cyclophosphamide, and rituximab remains the standard front-line therapy in fit patients with chronic lymphocytic leukaemia, but bendamustine and rituximab is associated with less toxic effects. Funding: Roche Pharma AG, Mundipharma, German Federal Ministry of Education and Research.